HAKEKAT ILMU HUKUM DITINJAU DARI FILSAFAT ILMU - Ida R. Hasan (Jurnal Ilmiah Hukum DE'JURE: Kajian Ilmiah Hukum, 2019)
One of the characteristic of law as a sui generis is has a wide scope of the field of study which consist three phase; legal dogmatics, legal theory, and legal philosophy. The rationality of legal dogmatics is explained by legal theory and the rationality of legal theory is explained by legal philosophy, so that the position of legal philosophy has two explanation of the rationality of legal dogmatics. This study uses normative legal research, using legal materials as a basis for studies to explain the problem. The results of this study confirm that the philosophy of law examines values, propierty, and balance. Legal theory examines that the teaching of law, the principles, concepts, and legal adage. And legal dogmatics studies the norms contained in written and unwritten rules that exist.